Characterization of Diaporthe batatas Harter & E.C. Field causing leaf spot in water spinach. - Garcia, T. A. P.; Montecalvo, M. P. (International Journal of Agricultural Technology, 2025)
Water spinach (Ipomoea aquatica Forsk.) is important for its nutritional, economic, and environmental benefits. However, pathogen infections can impact its production. This study aimed to identify the fungal pathogen responsible for leaf spots on lowland water spinach. Infected leaves showed brown necrotic spots surrounded by yellow halos. Pathogenicity assays confirmed the virulence of the fungal pathogen WS1 in both lowland and upland water spinach. Through morphological, cultural, and molecular characterization, the pathogen was identified as Diaporthe batatas Harter & E.C. Field. Key characteristics of the fungal isolate included hyaline, septated, and branched hyphae, with conidia measuring 4.1 to 8.3 µm in length and 1.8 to 3.2 µm in width. The isolate displayed distinct growth patterns on various artificial media with transparent, flat, rhizoid mycelium on water agar; white, velvety mycelium with black pycnidia on malt extract agar and potato dextrose agar; and dark brown to black filamentous colonies on Sabouraud dextrose agar. Sequencing of the internal transcribed spacer (ITS) and β-tubulin genes matched reference sequences of D. batatas. The study identifies D. batatas as a fungal pathogen of water spinach.